1973
DOI: 10.4141/cjss73-005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pipeline Installation on Soil Properties and Productivity

Abstract: or IoNc, E. lNo Burrox, R. G. 1973. Effects of pipeline installation on soil properties and productivity. Can. J. Soil Sci. 53: 37-47. The effects of pipeline installation on soil productivity were studied on mediumtextured Chernozemic and Solonetzic soils in southeastern Saskatchewan. Chemical and physical soil properties and wheat yields were measured for the undisturbed field, the trench, and the area adjacent to the trench used for soil storage during pipeline installation (the claybank). In general, Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 4 publications
2
24
0
Order By: Relevance
“…These were the soil chemical properties most affected by pipeline installation. Increases in pH, EC, sulphate, Ca, and Na in surface soil layers of pipeline RoWs have been reported previously (De Jong and Button 1973;Naeth et al 1987;Landsburg 1989). Therefore, the Grey soils of the boreal plain tend to be similar to Chernozemic and Solonetzic soils of the prairie with respect to changes in soil chemical properties in response to disturbance associated with pipeline installation.…”
Section: Chemical Propertiesmentioning
confidence: 86%
See 3 more Smart Citations
“…These were the soil chemical properties most affected by pipeline installation. Increases in pH, EC, sulphate, Ca, and Na in surface soil layers of pipeline RoWs have been reported previously (De Jong and Button 1973;Naeth et al 1987;Landsburg 1989). Therefore, the Grey soils of the boreal plain tend to be similar to Chernozemic and Solonetzic soils of the prairie with respect to changes in soil chemical properties in response to disturbance associated with pipeline installation.…”
Section: Chemical Propertiesmentioning
confidence: 86%
“…These results are in agreement with those of Culley et al (1982) showing that RoW surface soils have higher D b than those of adjacent undisturbed soils. Naeth et al (1987) also reported that pipeline construction compacted the surface soils of solonetzic rangelands while De Jong and Button (1973) found that the D b of trench areas was not different from or slightly higher than those of undisturbed agricultural soils. In our study, tillage to prepare seedbed may have reduced differences in the D b of RoW topsoils.…”
Section: Physical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…De Jong and Button (1973) published the results of one such study done in southeastern Saskatchewan. They reported that both the physical and chemical characteristics of the soil were altered, but wheat yield either remained the same or increased after pipeline installation.…”
Section: Introductionmentioning
confidence: 99%